2012
DOI: 10.1155/2012/153863
|View full text |Cite
|
Sign up to set email alerts
|

Functional Avidity: A Measure to Predict the Efficacy of Effector T Cells?

Abstract: The functional avidity is determined by exposing T-cell populations in vitro to different amounts of cognate antigen. T-cells with high functional avidity respond to low antigen doses. This in vitro measure is thought to correlate well with the in vivo effector capacity of T-cells. We here present the multifaceted factors determining and influencing the functional avidity of T-cells. We outline how changes in the functional avidity can occur over the course of an infection. This process, known as avidity matur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
101
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(104 citation statements)
references
References 158 publications
(180 reference statements)
3
101
0
Order By: Relevance
“…The latter finding is consistent with the notion that high-avidity T cells may be susceptible to exhaustion and activation-induced cell death, as has been reported from studies in chronic infections. 47 In the cancer setting, however, the tumor antigen load may not be high enough to trigger this mechanism. In unpublished experiments, we have observed that some high-avidity clones alter their cytokine profile when stimulated with high antigen concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter finding is consistent with the notion that high-avidity T cells may be susceptible to exhaustion and activation-induced cell death, as has been reported from studies in chronic infections. 47 In the cancer setting, however, the tumor antigen load may not be high enough to trigger this mechanism. In unpublished experiments, we have observed that some high-avidity clones alter their cytokine profile when stimulated with high antigen concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…It is not known whether this would be an issue in the cancer setting. Most investigators consider that high-affinity TCRs are desirable for cancer eradication, [47][48][49] whereas others have raised concerns regarding autoimmune side effects and also suggested that there is an affinity plateau which should not be exceeded. 41,50 We aim to use our comprehensive biobank of hTERT-reactive clones to develop a panel of TCRs with different affinities and assess their survival and functionality after infusion into patients.…”
Section: Discussionmentioning
confidence: 99%
“…Protective immunity against intracellular pathogens relies on the individual CD8 + T cell capacity to display multiple effector functions or polyfunctionality (10). We hypothesized that the kinetics of TCR-pMHC interactions could also affect their polyfunctionality.…”
Section: Tcr-pmhc Off-rate Accurately Correlates To Overall T Cell Fumentioning
confidence: 99%
“…Yet, others have challenged the functional superiority of such high-avidity cells, which may be prone to increased activation-induced cell death, senescence, or exhaustion (reviewed in ref. 10). In the context of antitumor responses, results obtained from melanoma patients also indicate that T cells of high functional avidities are required for efficient protection (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…The strength of binding between a T cell and the APC is crucial and is highly dependent on TCR affinity and structural avidity for the cognate MHC-peptide complex on the APC (10). However, the strength of the immunological synapse and functional avidity between a T cell and the APC are also affected by TCR-coreceptor expression, costimulatory receptor expression levels on T cell/APC, localization of TCR in lipid rafts, TCR signaling efficiency, and the local cytokine/inflammatory milieu among others (11,12). Despite this complexity, readouts for functional avidity are rather straightforward; they measure the Ag concentration required to activate T cells as assessed by functional assays, including cytokine production, proliferation, and target cell lysis.…”
Section: N Ovel Vaccine Candidates Have Traditionally Been Evaluatedmentioning
confidence: 99%